Att äterkomma tili nollpunkten - nägra tendenser i den postmoderna svenska och danska poes in - Niewiarowska-Rasmussen, Ewa (Folia Scandinavica Posnaniensia, 2007)
The paper presents main trends in the contemporary Swedish and Danish postmodern poetry represented by the generation of poets who made their debut in the 1980s. In the author’s opinion the poems are characterised by the diffuse persona of the speaker, rich intertextuality, the blending of literary genres and the focus on poetic language exposed to various experiments and analyses. For a postmodern poet a poem is not a ready-made product but rather a stage in an incessant process, it is both creative and unrestricted.